Impact of Conventional Cattle Farming Systems on Farmer Awareness, Livestock Output and Household Income - Iyai, D. A.; Nurhayati, D.; Pakage, S.; Widayati, I. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
Cattle was introduced in Papua a long time ago. However, it was unpredictable to adapt to raise cattle.An explorative field study was performed in fifteen villages using participatory research to betterunderstand the dynamics of cattle performances. Cattle farming system has been categorized in threetypes, i.e. small- and medium-sized systems. They used ANOVA and Kruskal-Wallis to analyze data. Thefinding of this research was that the three sizes of cattle farming in many components of good farmingpractices were similar (p>0.05). No large gap was found along the lines of farmers, cattle, and economicperformance. West New Guinea’s Tropical Livestock Unit was low and has the potential to increase dueto agribusiness potential. Better government services and other related stakeholders should narrow thelack of good agricultural practices.